Identifying variables dependency that influences a high level deliberation process in a CI-based Multi-Agent System - Gunasekaran S.S.; Mostafa S.A.; Ahmad M.S.; Tang A.Y.C. (Institute of Electrical and Electronics Engineers Inc., 2023)
Agents; Intelligent agents; Robotics; Collective intelligences; Cross fertilization; deliberation; intelligence; personal intelligence; Multi agent systems